2017
DOI: 10.4236/jbm.2017.512010
|View full text |Cite
|
Sign up to set email alerts
|

Factors and Pattern of Injuries Associated with Road Traffic Accidents in Hilly District of Nepal

Abstract: Introduction: In 21 st century, road traffic accidents (RTA) are considered as increasing epidemic of non-communicable disease which is abandoned and needs special attention to prevent them. The aim of this study was to assess the factors and pattern of injuries associated with road traffic accidents. Methods: A cross sectional study was conducted among 112 RTA victims and 56 drivers in Palpa District of Nepal. The association of factors and pattern of injuries with exposure to accidents was assessed using Fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 20 publications
(17 reference statements)
1
25
2
Order By: Relevance
“…[ 20 ] Shrestha found that head injury (41.1%) was the commonest injury followed by fracture (25.9%), external injury (like abrasion, lateration, cut injuries), and spinal injury. [ 17 ] Our findings were contrary to the study conducted by Ravikiran in Mangalore who observed that the most common site of injury was the abdomen (49%). [ 21 ] According to the Al-Thaifani study, fracture (47.81%) was the most common type of injury in the victims of RTI, followed by internal hemorrhage (29.5%) and cut wound/laceration (9.62%).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…[ 20 ] Shrestha found that head injury (41.1%) was the commonest injury followed by fracture (25.9%), external injury (like abrasion, lateration, cut injuries), and spinal injury. [ 17 ] Our findings were contrary to the study conducted by Ravikiran in Mangalore who observed that the most common site of injury was the abdomen (49%). [ 21 ] According to the Al-Thaifani study, fracture (47.81%) was the most common type of injury in the victims of RTI, followed by internal hemorrhage (29.5%) and cut wound/laceration (9.62%).…”
Section: Discussioncontrasting
confidence: 99%
“…Shrestha's study found that two-wheelers (38.4%) were most commonly involved in RTA followed by four and six-wheeler. [ 17 ] It reflects that two-wheelers are the most common mode of transport in India. Maximum casualties on two-wheelers could be due to reckless driving, not wearing helmets, or not following traffic rules.…”
Section: Discussionmentioning
confidence: 99%
“…The rider’s age had a significant relationship with alcohol and other drug use before riding in a study in Ghana [ 40 ]. The male gender and morning time riding was positively associated with RTC [ 43 ]. In Africa, people who commonly engage in commercial motor riding are mainly young males.…”
Section: Discussionmentioning
confidence: 99%
“…It is imperative that riders are given appropriate training and constantly encouraged to observe RT regulations to minimize associated risk. These are particularly essential as other studies identify lack of skill or inexperience, long riding hours, and risk-taking behaviors such as the driving speed of above 60 km/hour to be associated with the collisions of young drivers [ 43 , 44 ]. The risk of severe injury related to RTC may increase with acute tiredness, sleepiness, chronic fatigue, psychoactive substance use, and careless driver behavior [ 6 , 9 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation